Doing justice : a prosecutor's thoughts on crime, punishment, and the rule of law - Bharara, Preet, 1968- (Alfred A. Knopf, 2019)
Preet Bharara has spent much of his life examining our legal system, pushing to make it better, and prosecuting those looking to subvert it. Bharara believes in our system and knows it must be protected, but to do so, we must also acknowledge and allow for flaws in the system and in human nature. The book is divided into four sections: Inquiry, Accusation, Judgment and Punishment. He shows why each step of this process is crucial to the legal system, but he also shows how we all need to think about each stage of the process to achieve truth and justice in our daily lives. Bharara uses anecdotes and case histories from his legal career--the successes as well as the failures--to illustrate the realities of the legal system, and the consequences of taking action (and in some cases, not taking action, which can be just as essential when trying to achieve a just result). Much of what Bharara discusses is inspiring--it gives us hope that rational and objective fact-based thinking, combined with compassion, can truly lead us on a path toward truth and justice. Some of what he writes about will be controversial and cause much discussion. Ultimately, it is a thought-provoking, entertaining book about the need to find the humanity in our legal system--and in our society.